Effect of Digital Marketing Implementation Towards Muslim Fashion Brand Awareness And Brand Image - Arvin Enditya Putra; Yosman Bustaman; Munawaroh Zainal (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
TDigital marketing has a positive impact on brand awareness and brand image. This can have a good effect on the economy as it can increase brand awareness and brand image of Muslim fashion brands. This good effect on the economy will translate into improved company performance in covid'19. This study aims to determine the influence of the company's digital marketing on brand awareness and brand image on covid'19 in Muslim fashion brands. This study uses multiple regression on panel data from a sample of 100 respondents based in Indonesia. The variable of this research is digital marketing in Muslim fashion brands, and other variables are brand awareness and brand image to see what effect digital marketing has on these variables in covid'19. The results of the study resulted in t value > t table and sig < 0.05 from each hypothesis that everything was declared accepted because t value > t table and sig < 0.05. This study shows that there is a significant influence on digital marketing on Muslim fashion brands on brand awareness and brand image in the covid'19 pandemic